2016
DOI: 10.1016/j.foodcont.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of good hygiene practices intervention on food safety in senior secondary schools in Ghana

Abstract: Get rights and content Highlights•Good hygiene practices intervention in the form of training improved kitchen staff hygiene awareness scores.•Staff temperature and time monitoring for ready to eat (RTE) meals' significantly improved after training.•Microbiological contaminants (ACC, coliforms, yeast and moulds, Staphylococcus aureus and Bacillus cereus) in RTE meals reduced with a significant reduction in Aerobic Colony Count (ACC) and Staphylococcus aureus levels after training. AbstractEleven schools in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…The intervention group, which was aided by an external food professional, showed greater improvement than the control group in the second evaluation. These results are similar to the ones found in the studies by da Cunha et al (2013) and Ababio et al (2016) Although positive adjustments were observed in the second evaluation, the adequacy of Categories 5 and 8 remained low in the control group. Furthermore, Category 8's adequacy percentage was also low in the intervention group.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The intervention group, which was aided by an external food professional, showed greater improvement than the control group in the second evaluation. These results are similar to the ones found in the studies by da Cunha et al (2013) and Ababio et al (2016) Although positive adjustments were observed in the second evaluation, the adequacy of Categories 5 and 8 remained low in the control group. Furthermore, Category 8's adequacy percentage was also low in the intervention group.…”
Section: Discussionsupporting
confidence: 90%
“…The intervention group, which was aided by an external food professional, showed greater improvement than the control group in the second evaluation. These results are similar to the ones found in the studies by da Cunha et al () and Ababio et al () in schools; Serafim et al () in hotels; de Jesus et al () in a food transport company; Stangarlin‐Fiori et al () in hospital feeding units; and Barjaktarović‐Labovic et al () in the food industry. Therefore, the aid of a food safety expert contributes effectively to the implementation of good hygiene practices in the food truck and other foodservice segments.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Studies conducted in food establishments also revealed significant improvements after an intervention strategy, suggesting that the companies adopt these programs in a continuous manner, because they help to motivate the work staff and thus lead to continuity in compliance with the Good Hygiene Practices (Rodrigues et al, 2012;Cunha et al, 2013;Ababio et al, 2016). Therefore, up-to-date, systematic and impartial information allows a change in behavior of individuals and identifies errors that may not be perceived during work routines, minimizing the risk of food contamination (Faour-Klingbeil et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in food establishments in Brazil and other countries have revealed that after the implementation of Good Hygiene Practices there was a decrease in non-conformities with hygienic-sanitary criteria and positive changes in the behavior of administrators and food handlers (Rodrigues et al, 2012;Ababio et al, 2016). Nevertheless, the implementation of the program can be harmed by the absence of technical knowledge among those who are responsible for the establishment, or by the fact that the people with technical responsibility for food handling are accustomed to the existing non-conformities in the work environment (Faour-Klingbeil et al, 2015).…”
Section: Introductionmentioning
confidence: 99%